Clinical and Diagnostic Significance of Metabolic Dysfunction and Liver Fibrosis Stages in Patients with Non-Alcoholic Fatty Liver Disease (NAFLD) - Isroilov , Muhammadali; Soliyev , Alisher (INTERNATIONAL MULTIDISCIPLINARY SCIENCE CONFERENCE, 2026)
Background: Non-alcoholic fatty liver disease (NAFLD) is a leading cause of chronic liver disease worldwide. Methods: A prospective study of 84 patients was conducted to evaluate the link between metabolic markers and fibrosis. Liver stiffness was measured using transient elastography (FibroScan). Results: A significant correlation was found between HOMA-IR and fibrosis stage (r=0.58, p30 kg/m² showed a 2.4-fold higher risk of advanced fibrosis (95% CI: 1.8–3.2).Conclusion: Early metabolic intervention is crucial to prevent progression to cirrhosis. [112 words]